Literature Review: Antioxidant Test of Basil Leaves (Ocimum Sanctum) - Noka Riyani; Kusumaningtyas Siwi Artini; Tatiana Siska Wardani (Proceeding of International Conference on Science, Health, And Technology, 2021)
Basil leaves is family of lamiaceace, which is known as daun kemangi (Indonesia). This plant is widely use as a herb. Indonesian also used basil leaves as a seasoning in their food. It has chemical compound such as flavonoid so it has an antioxidant effect. The aim of this reseach is to find out the antioxidant effect of the basil leaves, the chemical compound of basil leaves. The method by reviewing online articles at Pubmed, sciencedirect and Google Scholar. Cemichal compound wes identified in some reseach. It show different potential base on the extraction proses. The antioxidant effect was tested using the DPPH method for determination of IC50. By reviewing articles, we can conclude that basil leaves have an antioxidant effect.